2019
DOI: 10.15294/eeaj.v7i3.28333
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Kewirausahaan, Business Center Dan Kreativitas Siswa Terhadap Jiwa Berwirausaha Siswa

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh secara parsial dan simultan antara pendidikan kewirausahaan, business center dan kreativitas terhadap jiwa berwirausaha.Populasi dalam penelitian ini adalah siswa kelas XI jurunsan pemasaran SMK Negeri 1 Slawi yang berjumlah 134 dengan jumlah sampel 58 peserta didik yang dihitung dengan rumus slovin. Metode pengumpulan data menggunakan angket/kuesioner. Metode analisis data menggunakan analisis deskriptif presentase dan analisis regresi berganda. Hasil penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
3
0
3
Order By: Relevance
“…For VHS teachers, the BC acted as a representative simulation place to teach entrepreneurship material. In the previous research, it was shown that entrepreneurial learning using BCs makes teachers have a more effective role and time in teaching [32], [7].…”
Section: Discussionmentioning
confidence: 99%
“…For VHS teachers, the BC acted as a representative simulation place to teach entrepreneurship material. In the previous research, it was shown that entrepreneurial learning using BCs makes teachers have a more effective role and time in teaching [32], [7].…”
Section: Discussionmentioning
confidence: 99%
“…Kreativitas adalah kemampuan seseorang untuk menemukan sebuah peluang yang ada dan mengembangkan ide-ide baru dalam memecahkan suatu masalah yang ada maupun yang belum ada agar meminimalisir kegagalan dalam melakukan pekerjaannya (Rimadani & Murniawaty, 2019). Program Kreativitas Mahasiswa (PKM) yang tiap tahun dipastikan hadir dalam dunia kampus menjadi wadah mahasiswa dalam mengasah kemampuan nalar dan kreativitas dalam merumuskan sebuah rancangan produk yang dibutuhkan masyarakat.…”
Section: Pendahuluanunclassified
“…(Yordanova and Filipe, 2019) Answering the problem of unemployment in Indonesia, EEPs needs to be managed more seriously and transformed not just to change the mindset of society into a more concrete program as term solution. Research has proven the success of EEPs in changing EM in Indonesia, among others, have been carried out by (Arifin and Prasetyaningtyas, 2018), (Alfiyan et al, 2019), (Dijayanti, 2017), (Rusmana, 2020), (Indriyani, 2018), (Wijayanto and Prasetyo, 2018), (Santy et al, 2017), (Rimadani and Murniawaty, 2019), (Purusottama and Trilaksono, 2019). The answer is, do EEPs in Indonesia's higher education only stop at the formation of EM?…”
Section: Literature Reviewmentioning
confidence: 99%